Growth with resilience for Viksit Bharat 2047: conversations around water, energy and livelihood security - Raut, Oorna; Verma, Shilp; Sneha, S. B. (International Water Management Institute, 2025)
The IWMI-Tata Partners’ Meet 2024 brought together over 270 national and international participants to deliberate on critical issues at the intersection of water, energy, climate, agriculture, and rural livelihoods in India. Organized by the IWMI-Tata Water Policy Program, a co-equal partnership between IWMI and Tata Trusts, this flagship event featured curated plenary sessions and 18 technical sessions across four thematic tracks: [1] Water-Energy-Livelihoods Nexus; [2] Catalyzing Smallholder Prosperity; [3] Water Governance and Risks; and [4] Emerging Themes. Compiling and synthesizing conversations around these thematic areas, this report offers an in-depth account of the presentations, discussion threads, and field learnings that shaped the 2024 Partners’ Meet. It serves both as a record of deliberations and of the diverse ideas, insights, and evidence shared by the participants.